2019
DOI: 10.1103/physrevd.100.055014
|View full text |Cite
|
Sign up to set email alerts
|

Planck scale origin of nonzero θ13 and super-WIMP dark matter

Abstract: We study a discrete flavour symmetric scenario for neutrino mass and dark matter under the circumstances where such global discrete symmetries can be explicitly broken at Planck scale, possibly by gravitational effects. Such explicit breaking of discrete symmetries mimic as Planck suppressed operators in the model which can have non-trivial consequences for neutrino and dark matter sectors. In particular, we study a flavour symmetric model which, at renormalisable level, gives rise to tri-bimaximal type neutri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 135 publications
0
3
0
Order By: Relevance
“…In [223] the authors have shown that such tiny coupling required in both dark and visible sectors may have its origin in A 4 discrete flavor symmetry. In another effort [224] it has been shown that the non-zero value of the reactor mixing angle θ 13 can originate from a Planck scale suppress operators and as well as realize super-WIMP dark matter scenario. The study of dark matter in the context of non-Abelian discrete symmetries demands a lot more attention to explore the connection of neutrino physics and dark matter, if any.…”
Section: A Flavor Symmetry and Dark Mattermentioning
confidence: 99%
“…In [223] the authors have shown that such tiny coupling required in both dark and visible sectors may have its origin in A 4 discrete flavor symmetry. In another effort [224] it has been shown that the non-zero value of the reactor mixing angle θ 13 can originate from a Planck scale suppress operators and as well as realize super-WIMP dark matter scenario. The study of dark matter in the context of non-Abelian discrete symmetries demands a lot more attention to explore the connection of neutrino physics and dark matter, if any.…”
Section: A Flavor Symmetry and Dark Mattermentioning
confidence: 99%
“…Gauge structure of the underlying theory dictates the structure of these non-renormalisable operators. Role of such operators on neutrino mass and mixing has been discussed in [76][77][78].…”
Section: Domain Walls In Lrsmmentioning
confidence: 99%
“…This has led to several proposals that attempt to generate tiny Dirac neutrino masses in a variety of ways . In a recent work [90], a common origin of light Dirac neutrinos and non-thermal DM was proposed where tiny couplings involved in non-thermal DM and Dirac neutrino mass had common source from higher dimensional operators. Here we extend that idea to incorporate inflation as well 1 , within a modified chaotic inflation scenario.…”
Section: Introductionmentioning
confidence: 99%